Association between Type 1 Diabetes Mellitus and Graves' Disease: A review - Pedro Miguel Marques Duarte Couto (2021)
Type 1 Diabetes Mellitus and Graves' Disease are two main diseases in Endocrinology presenting both a considerable level of morbidity. The literature strongly suggests that these two conditions are commonly found in the same patient. This is partially explained by the fact that an autoimmune disease is a risk factor to the appearance of another one. However, the current literature shows several potential different specific mechanisms that may trigger the development of Graves' Disease on a patient with Type 1 Diabetes Mellitus and vice-versa. Accordingly, in this review, we will summarize the current evidence on these specific mechanisms, as well as the state of the art on this topic.